Glosa do wyroku Trybunału Sprawiedliwości Unii Europejskiej w sprawie MJ vs. AA z dnia 24 marca 2026 r., sygn. akt C-521/21 dotyczącego możliwości wyłączenia sędziego sądu powszechnego od orzekania z powodu okoliczności jego powołania - Wojciechowski, Bartosz; Liżewski, Bartosz (PRAWO i WIĘŹ, 2026)
The judgment of the Court of Justice of the European Union under discussion concerns the compatibility of the appointment of judges in Poland after 2018 with the second subparagraph of Article 19(1) of the TEU and the second paragraph of Article 47 of the Charter of Fundamental Rights of the European Union. The Court held that, although the National Council of the Judiciary in its new composition does not provide sufficient guarantees of independence to dispel all reasonable doubts as to the regularity of the procedures for appointing judges, and although the right to appeal resolutions of the National Council of the Judiciary to the Supreme Court (Chamber of Extraordinary Control and Public Affairs) in the nomination process cannot be considered an effective remedy, other relevant circumstances surrounding the appointment of a given judge must also be examined tolegitimately conclude that he or she does not meet the requirement of an “independent and impartial court.” The authors take a critical stance towards the conclusions drawn from the above judgment, which, in their view, does not resolve the validity of judicial appointments made after 2018. The Court of Justice’s calls for this issue to be resolved through legislation are clear, but they do not bring us any closer to resolving the existing tension and conflict.